Natural variation and domestication selection of ZmSULTR3;4 is associated with maize lateral root length in response to salt stress - Zhang, Xiaomin; Zhu, Tianze; Li, Zhi; Jia, Zhongtao; Wang, Yunyun; Liu, Runxiao; Yang, Mengling; Chen, Qing-Bin; Wang, Zhenjie; Guo, Siyi; Li, Pengcheng (Frontiers in Plant Science, 2022)
Soil salinity is a major constraint that restricts crop productivity worldwide. Lateral roots (LRs) are important for water and nutrient acquisition, therefore understanding the genetic basis of natural variation in lateral root length (LRL) is of great agronomic relevance to improve salt tolerance in cultivated germplasms. Here, using a genome-wide association study, we showed that the genetic variation in ZmSULTR3;4, which encodes a plasma membrane-localized sulfate transporter, is associated with natural variation in maize LRL under salt stress. The transcript of ZmSULTR3;4 was found preferentially in the epidermal and vascular tissues of root and increased by salt stress, supporting its essential role in the LR formation under salt stress. Further candidate gene association analysis showed that DNA polymorphisms in the promoter region differentiate the expression of ZmSULTR3;4 among maize inbred lines that may contribute to the natural variation of LRL under salt stress. Nucleotide diversity and neutrality tests revealed that ZmSULTR3;4 has undergone selection during maize domestication and improvement. Overall, our results revealed a regulatory role of ZmSULTR3;4 in salt regulated LR growth and uncovered favorable alleles of ZmSULTR3;4, providing an important selection target for breeding salt-tolerant maize cultivar.